Antimicrobial resistance reservoirs in salmon and broiler processing environments, sidestreams, and waste discharges - Reiche, Thorben; Jakobsen, Anita Nordeng; Mares, Mihai; Hoel, Sunniva; Tøndervik, Anne; Heggeset, Tonje Marita Bjerkan; Haugen, Tone; Tømmerdal, Andreas Husby; Broli, Gunn; Butt, Husnain Amir; Bårdsen, Iris Olene; Hageskal, Gunhild (Frontiers in Microbiology, 2025)
Mapping reservoirs of antimicrobial resistance (AMR) across food value chains and their environmental dissemination pathways is essential for limiting the spread and impact of AMR. The aim of this study was to investigate the prevalence of AMR genes and bacteria in sidestream materials, waste discharges, and processing environments of salmon and broiler. A targeted hybrid capture-based sequencing approach was used to characterize the resistome in samples collected from four processing plants, revealing a diverse range of AMR genes. Among these, we found several high-risk AMR genes, including the multidrug resistance genes TolC and mdtE, tetracycline genes tet(L) and tet(M), aminoglycoside genes APH(3′)-IIIa and APH(6)-Id, and beta-lactam genes mecA and mecR1. Overall, the highest numbers of AMR genes were found in samples of process wastewater and sludge, ranging from 32 to 330 unique genes. More than 300 bacterial isolates, including Enterobacterales, Enterococcus and Pseudomonas spp. were also collected and identified, and a subset was tested for antibiotic susceptibility. Antibiotic resistance among Enterococcus and Pseudomonas spp. was low. Quinolone-resistant Escherichia coli (QREC) were detected in waste discharges from two broiler processing plants, while multidrug resistant (MDR) E. coli were found only in one plant. Whole genome sequencing of MDR isolates revealed multiple plasmids and AMR genes such as sul2, ant(3″)-Ia, qnrS1, and blaCTX-M-1. Our study highlights that wastewater from food industries can contribute to the release of AMR bacteria and genes to the environment. While the prevalence of AMR bacteria in sidestream materials was low among the isolates in our collection, numerous AMR genes were detected, which may be re-introduced to new production systems.